2006
DOI: 10.1016/j.dnarep.2006.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Gaps and forks in DNA replication: Rediscovering old models

Abstract: (2006) Gaps and forks in DNA replication: Rediscovering old models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(128 citation statements)
references
References 17 publications
8
119
1
Order By: Relevance
“…The ratio of kan R /cm R E. coli colonies is a measure of the efficiency of TLS in the mammalian cells, and sequence analysis of plasmids extracted from individual colonies provides data on DNA sequence changes during TLS. The assay was found to be very useful to study TLS in mammalian cells (8,16,17), perhaps because it is a good model system of postreplication gaps (18). Using this system we have shown that TLS across a TT CPD is an order of magnitude more mutagenic in XPV cells compared with normal cells (19), consistent with the hypermutability of XPV cells (12), and the relatively accurate TLS across CPD by purified pol (10,20).…”
Section: Resultssupporting
confidence: 50%
“…The ratio of kan R /cm R E. coli colonies is a measure of the efficiency of TLS in the mammalian cells, and sequence analysis of plasmids extracted from individual colonies provides data on DNA sequence changes during TLS. The assay was found to be very useful to study TLS in mammalian cells (8,16,17), perhaps because it is a good model system of postreplication gaps (18). Using this system we have shown that TLS across a TT CPD is an order of magnitude more mutagenic in XPV cells compared with normal cells (19), consistent with the hypermutability of XPV cells (12), and the relatively accurate TLS across CPD by purified pol (10,20).…”
Section: Resultssupporting
confidence: 50%
“…The ssDNA gap would then be filled by pol IV, by other polymerases such as pol V or pol II, or even by pol III*. Consistent with this speculation, it has been shown that a replication fork keeps moving even when a lesion exists on both strands in vivo, leaving an ssDNA gap behind it (30,31). Heller and Marians showed (32) that the primase bound to DnaB helicase on the lagging strand can prime on the leading strand in vitro, implying that the replication fork restarts on the leading strand.…”
Section: Discussionmentioning
confidence: 58%
“…In some instances, replication may be restarted downstream of the unrepaired parental strand lesion, leaving a "daughter strand gap" (DSG)-a ssDNA lesion that cannot be filled by a conventional DNA polymerase, due to the presence of the DNA polymerase blocking lesion. The DSG has received less attention than its illustrious cousin, the DSB, but recent work in model organisms has reawakened interest in the DSG as a potential intermediate in genomic instability and cancer [7]. DSBs and DSGs can be repaired in an error-free manner by sister chromatid recombination (SCR), a mechanism whereby the damaged chromatid uses the intact sister as a template for repair by homologous recombination (HR) [5,8,9].…”
Section: Introductionmentioning
confidence: 99%